2004
DOI: 10.1210/jc.2003-030995
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of the N363S Polymorphism of the Glucocorticoid Receptor in South Asians Living in the United Kingdom

Abstract: Similarities between clinical states of glucocorticoid excess and obesity have raised suspicion of a link between the two conditions. An Asn363Ser (N363S) polymorphism in exon 2 of the glucocorticoid receptor has been associated with glucocorticoid sensitivity and excess adiposity in people of European origin. Compared with Europid populations, South Asians have a higher prevalence of cardiovascular risk factors, including type 2 diabetes and central obesity. The aim of this study was to determine the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…Our data are in accordance to studies in randomly selected European populations, which have reported a frequency of the 363S allele of 3-7% (20,(26)(27)(28)(29). Interestingly, we observed no 363S allele in Brazilian subjects of Asian origin, similar to a study in South Asian subjects living in the United Kingdom, in which the 363S allele frequency was very low (0.3%) (30). Recently, the p.N363S polymorphism was neither detected in a Japanese population (31) nor in Chinese Han individuals, a subset of Asian-origin population (32).…”
Section: Resultssupporting
confidence: 91%
“…Our data are in accordance to studies in randomly selected European populations, which have reported a frequency of the 363S allele of 3-7% (20,(26)(27)(28)(29). Interestingly, we observed no 363S allele in Brazilian subjects of Asian origin, similar to a study in South Asian subjects living in the United Kingdom, in which the 363S allele frequency was very low (0.3%) (30). Recently, the p.N363S polymorphism was neither detected in a Japanese population (31) nor in Chinese Han individuals, a subset of Asian-origin population (32).…”
Section: Resultssupporting
confidence: 91%
“…The observed allele frequencies were consistent with those reported elsewhere for Caucasian populations [11][12][13][14] . The distribution of the alleles and genotypes did not differ between control and patient groups (supplementary materials, Table 3).…”
Section: Resultssupporting
confidence: 91%
“…21,22) In the coding region, a novel nonsynonymous variation, 420GÀT (Lys140Asn), was detected in exon 2. 24) Their report and our present data clearly indicate that ethnic dierences between Asian and other populations exist for the Asn363Ser polymorphism. The electropherograms of the variation is shown in Fig.…”
Section: Resultssupporting
confidence: 74%